2007
DOI: 10.1111/j.1442-9071.2007.01629.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between second‐generation frequency doubling technology and standard automated perimetry in patients with glaucoma

Abstract: Generally, the Matrix and Humphrey Field Analyser perimetry correlate well; however, each machine utilizes a different method of analysing data and thus the direct comparison should be made with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
1
5
1
Order By: Relevance
“…Subdivided into quadrants, only the nasal inferior quadrant in healthy subjects (r = 0.53, p<0.005) and the temporal inferior and nasal inferior quadrants in ocular hypertensive subjects (r = 0.45 and r = 0.53, p≤0.005) were significantly correlated. This differs from the results reported by Zarkovic et al [6] who reported the highest correlation in glaucoma patients in the superior hemifields and supero-nasal quadrants.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Subdivided into quadrants, only the nasal inferior quadrant in healthy subjects (r = 0.53, p<0.005) and the temporal inferior and nasal inferior quadrants in ocular hypertensive subjects (r = 0.45 and r = 0.53, p≤0.005) were significantly correlated. This differs from the results reported by Zarkovic et al [6] who reported the highest correlation in glaucoma patients in the superior hemifields and supero-nasal quadrants.…”
Section: Discussioncontrasting
confidence: 99%
“…Other investigations found good correlations between SAP and Matrix-FDT in glaucoma patients. [1], [6], [9], [10] Artes et al compared SAP and Humphrey Matrix in a small study of 15 glaucoma patients. Their global visual field indices mean deviation (MD) and pattern standard deviation (PSD) correlated highly (r = 0.86, p<0.001; r = 0.95, p<0.001, repectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with the previous studies, 16,18 we found the test duration of FDT-Matrix to be significantly shorter than that of SAP-SITA. This difference may be explained by the different algorithms used by these tests.…”
supporting
confidence: 82%